2019
DOI: 10.1093/infdis/jiz487
|View full text |Cite
|
Sign up to set email alerts
|

Quinine Enhances Photo-Inactivation of Gram-Negative Bacteria

Abstract: Background Antimicrobial resistance is a significant concern to public health, and there is a pressing need to develop novel antimicrobial therapeutic modalities. Methods In this study, we investigated the capacity for quinine hydrochloride (Q-HCL) to enhance the antimicrobial effects of antimicrobial blue light ([aBL] 405 nm wavelength) against multidrug-resistant (MDR) Gram-negative bacteria in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…1A and 3C). 305 Recently, studies of photodynamic therapy (PDT) have revealed light, simultaneously applied with antibiotics, as a potentiator of biofilm infection eradication (49)(50)(51). Our finding that PYO, also classified as an antibiotic (52), in conjunction with light diminishes biofilm integrity is consistent with the notion that an oxidizing environment, which is often created as a result of antibiotic treatment, and light together enhance remediation of biofilm-based infections.…”
Section: Phosphodiesterases (Pdes) Contribute To the Light-dependent supporting
confidence: 79%
“…1A and 3C). 305 Recently, studies of photodynamic therapy (PDT) have revealed light, simultaneously applied with antibiotics, as a potentiator of biofilm infection eradication (49)(50)(51). Our finding that PYO, also classified as an antibiotic (52), in conjunction with light diminishes biofilm integrity is consistent with the notion that an oxidizing environment, which is often created as a result of antibiotic treatment, and light together enhance remediation of biofilm-based infections.…”
Section: Phosphodiesterases (Pdes) Contribute To the Light-dependent supporting
confidence: 79%
“…During aBL irradiation, the bacterial suspension was stirred using a 12-mm magnetic bar (20 rpm) to prevent sedimentation. A total of four aliquots of aBL were delivered (27, 54, 81 and 108 J/cm 2 ) and 30 µL of the suspension was withdrawn following each aliquot to determine the CFU as described previously (19). Experiments were performed in triplicate.…”
Section: Abl+q-hcl Inactivation Of Planktonic C Albicans In Vitromentioning
confidence: 99%
“…Quinine is a potent antimalarial compound that has been shown to have inherent antibacterial and antifungal properties, albeit at high concentrations (16)(17)(18). In a previous study, we found Q-HCL to significantly enhance the effects of aBL in Gram-negative bacteria (19), Therefore, in this study we investigated the combined use of aBL and quinine hydrochloride for the inactivation of C. albicans, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Confronted with this dire situation, antimicrobial blue light has emerged as a novel approach to combat multidrug-resistant bacterial infections 5,6 . Blue light in the 405-420 nm or the 450-470 nm optical windows has demonstrated bactericidal effects towards a wide range of microbial species, including gram-positive bacteria, gram-negative bacteria, mycobacteria, and molds 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Blue light has also been allied with other antimicrobial agents to eradicate bacteria. For example, quinine in combination with blue light exposure has shown efficacy to eliminate gram-negative P. aeruginosa, Acinetobacter baumannii ( A. baumannii ) 5 and Candida albicans 14 . Blue light irradiance was also reported to enhance the inactivation efficacy of low-concentration chlorinated disinfectants towards Clostridium difficile 15 .…”
Section: Introductionmentioning
confidence: 99%